HUBUNGAN KEBIJAKAN, SARANA DAN PRASARANA DENGAN KESIAPSIAGAAN KOMUNITAS SEKOLAH SIAGA BENCANA BANDA ACEH - Rina Susanti; Sri Adelila Sari; Sri Milfayetty; M. Dirhamsyah (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2014)
Abstract: This study aims to determine the relationship of policies, as well as facilities and infrastructure to the level of community preparedness Disaster Preparedness School (SSB). This study used a descriptive approach-quantitative method. This study was conducted in one school pilot disaster preparedness, which is SDN 2 in Banda Aceh. Its population is a school community that is actively involved in all activities related to Disaster Risk Reduction (DRR) in school. Data were collected by questionnaire using parameters preparedness. Data were analyzed with descriptive statistics and correlation tests. The results showed that the level of community preparedness categorized SSB; very prepared for disasters. This is supported by the significant relationship between the parameters of preparedness with DRR programs that have been implemented at the school. From the results of this study concluded that the implementation of DRR related to the level of preparedness of the school community. Keywords: Disaster Risk Reduction , preparedness , school community